Spiritual politics changing the world from the inside out - McLaughlin, Corinne; Davidson, Gordon 1944- (Ballantine Books, a division of Random House, Inc., 1994)
In this profound and revolutionary work, veteran social activists Corinne McLaughlin and Gordon Davidson shift the focus of political dialogue from the "evening news" to the hidden spiritual causes of world affairs. We begin to understand what events like the dissolution of the Soviet Union, the Clarence Thomas hearings, and the national health crisis can tell us about deeper forces at work--including karma, reincarnation, and the "soul of nations." The key is recognizing the Divine hand behind human evolution. In the face of profound human crises, we learn to ask what spiritual lessons are being taught. SPIRITUAL POLITICS shows that each individual's inner work--meditation, prayer, visualization--can affect outer events. There is something each of us can do right here, right now, to change the world.